Advancing fracture fragility assessment of pre‐Northridge welded column splices. (15th December 2019) - Song, Biao; Galasso, Carmine; Kanvinde, Amit
Summary: A refined probabilistic assessment of seismic demands and fracture capacity of welded column splice (WCS) connections in welded steel moment resisting frames (WSMRFs) is presented. Seismic demand assessment is performed through cloud‐based nonlinear time history analysis (NLTHA) for two case‐study structures, i.e., a 4‐ and a 20‐ story WSMRFs. Results from NLTHA are used to derive fracture fragility of WCS connections. To this aim, the study investigates (1) optimal ground‐motion intensity measures for conditioning probabilistic seismic demand models in terms of global (i.e., maximum inter‐story drift ratio) and local (i.e., peak tensile stress in the flange of WCSs) engineering demand parameters of WSMRFs; (2) the effect of ground‐motion vertical components on the longitudinal flange stress of WCS connections and their resulting fracture fragility; and (3) the effect of WCS capacity uncertainties on the fracture fragility estimates of those connections. For the latter case, an advanced finite element fracture mechanics‐based approach proposed by the authors is employed to capture aleatory and epistemic uncertainties affecting fracture capacities. The focus is on pre‐Northridge WCS connections featuring partial joint penetration and brittle materials, making them highly vulnerable to seismic fracture. Fracture fragility results for the case‐study structures are compared and discussed, highlighting the importance of the considered issues on fragility estimates, particularly in the case of high‐rise structures. Findings from the study contribute shedding some light on the influence of seismic demand and capacity uncertainties on the assessment of fracture fragility of WCS connections. These findings can guide similar performance‐based assessment exercises for WSMRFs to inform, for instance, the planning and design of retrofitting strategies for those vulnerable connections.